Fancy Nancy splendiferous Christmas - O'Connor, Jane (O'Connor, Jane. Fancy Nancy., 2009)
Nancy is devastated, which is even worse than heart-broken, when her fancy Christmas tree topper breaks, threatening to ruin Christmas.